2021
DOI: 10.1007/s11356-021-15188-4
|View full text |Cite
|
Sign up to set email alerts
|

The asymmetric associations between foreign direct investment inflows, terrorism, CO2 emissions, and economic growth: a tale of two shocks

Abstract: Foreign direct investments can exert ambiguous effects on the environmental quality of the host economies. At the same time, terrorism is a worldwide phenomenon that affects human life, FDI inflows, economic growth, and, most importantly, environmental well-being. Hence, it can be expected that there are relationships between terrorism, foreign direct investment inflows, and carbon dioxide emissions. However, in the previous literature, less attention has been given to explore these nexuses. In addition, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 94 publications
1
33
0
Order By: Relevance
“…The research findings indicated the two leading sectors, i.e., GDP and FDI, as environmentally damaging, which pointed out that the unambiguous economic efficient system with positive climate change will exceed the action cost. This research also declared the economy's positive contributors and eco-friendly sectors, such as renewable energy consumption and production Bekun et al, 2021;Chishti et al, 2021;Paramati et al, 2022). This research suggests that state handlers should focus on eco-friendly sectors to enhance the financial position of their countries and sort out the problems and uncertainties of other sectors.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The research findings indicated the two leading sectors, i.e., GDP and FDI, as environmentally damaging, which pointed out that the unambiguous economic efficient system with positive climate change will exceed the action cost. This research also declared the economy's positive contributors and eco-friendly sectors, such as renewable energy consumption and production Bekun et al, 2021;Chishti et al, 2021;Paramati et al, 2022). This research suggests that state handlers should focus on eco-friendly sectors to enhance the financial position of their countries and sort out the problems and uncertainties of other sectors.…”
Section: Discussionmentioning
confidence: 77%
“…Agriculture is a contributor to GHG emissions and is sensitive to GHG release (IPCC 2007). The World Bank (2013) stated that between one-fourth and one-third of the world's total GHG emissions are generated by agriculture, from both on-farm operations, i.e., approximately 10%-12% of global emissions, and land use and land cover changes to cropland, including an additional 12%-20% (Mulatu et al, 2016;Bekun et al, 2021;Chishti et al, 2021). According to Malhi et al (2021), increased CO 2 levels resulted in improved crop fertilization and decreased energy requirements from heat (Eshete et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some of the literature that included the Philippines in their analysis of the impact of economic growth and FDI was the study conducted by Chishti et al (2021). Their findings revealed that pollution in the Philippines is worsened by the growth of GDP and FDI only in the short run.…”
Section: Still Inmentioning
confidence: 99%
“…Many studies have examined its impact on CO 2 emissions in developed and developing countries. Xingang et al (2019) and Chishti et al (2021) found a positive relationship between foreign direct investment and CO 2 emissions in developing countries. Jalal et al (2011) also found positive effects of foreign direct investment on CO 2 emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Extant literature on sustainable environment has looked into factors which have a relationship with environmental sustainability, like corporate social responsibility, globalization, renewable energy, industrialization, tourism, poverty, energy prices, internal trade, economic freedom, technology, human capital, health expenditure, remittance inflows, innovation, population, temperature, water scarcity, institutional quality, foreign direct investment, trade openness, and economic growth, among others (Meo et al, 2021;Sarkodie and Adams, 2018;Chishti et al, 2021). The last four factors are considered highly important factors for the growth of any country.…”
Section: Introductionmentioning
confidence: 99%